Increasing the Capacity of Mothers of Toddlers in Early Detection of Stunting in Quality Family Village, Bengkayang Regency - Novi Irawan; Marlenywati; Indah Budiastutik; Elly Trisnawati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Stunting is one of the serious nutritional problems experienced by toddlers in the world as well as toddlers in Indonesia. Stunting has a negative impact on the quality of life in the future because it can interfere with the growth and development of toddlers, and can affect children's learning abilities. One of the factors causing stunting is the lack of parental knowledge about the importance of nutritional status in children. Meanwhile, the problems found in the field are errors and inaccuracies in the use of anthropometric tools used by posyandu cadres. One of the efforts to detect early stunting can involve the participation of parents, especially mothers, an activity is needed that aims to improve mothers' skills by providing anthropometric training and stunting prevention education. Objective: Increase the knowledge capacity and skills of mothers of toddlers in efforts to detect early stunting with anthropometric measurement training and stunting prevention education in Quality Family Village, Bengkayang Regency. Method: This research is a quantitative study conducted directly with a Quasy experimental design of one group pre-test and post-test. The research was conducted in the Quality Family Village of Bengkayang Regency. The research sample was mothers who had toddlers who met the inclusion criteria. Samples were taken by purposive sampling. Data collection was carried out through direct interviews regarding the characteristics of respondents, taking anthropometric measurements on toddlers, filling out pre-test and post-test research questionnaires by mothers. Result: This study showed that there was a change in the mother's knowledge score before and after education was given. The pre-test score obtained was 3.87%. Meanwhile, the post-test score obtained was 5.78%. The results of measuring the mother's skill level score in conducting early detection of stunting. The mean value obtained was 1.70% before the intervention and then obtained a value of 4.98% after the intervention. Conclusion: This study concluded that there was an effect on the level of knowledge and skills of mothers before and after being given an intervention on early detection of stunting in the Quality Family Village (Kampung KB) Bengkayang Regency.